Ketone Body Acetoacetate Buffers Methylglyoxal via a Non-enzymatic Conversion during Diabetic and Dietary Ketosis. Issue 8 (17th August 2017) - Salomón, Trine; Sibbersen, Christian; Hansen, Jakob; Britz, Dieter; Svart, Mads Vandsted; Voss, Thomas Schmidt; Møller, Niels; Gregersen, Niels; Jørgensen, Karl Anker; Palmfeldt, Johan; Poulsen, Thomas Bjørnskov; Johannsen, Mogens
Summary: The α-oxoaldehyde methylglyoxal is a ubiquitous and highly reactive metabolite known to be involved in aging- and diabetes-related diseases. If not detoxified by the endogenous glyoxalase system, it exerts its detrimental effects primarily by reacting with biopolymers such as DNA and proteins. We now demonstrate that during ketosis, another metabolic route is operative via direct non-enzymatic aldol reaction between methylglyoxal and the ketone body acetoacetate, leading to 3-hydroxyhexane-2, 5-dione. This novel metabolite is present at a concentration of 10%–20% of the methylglyoxal level in the blood of insulin-starved patients. By employing a metabolite-alkyne-tagging strategy it is clarified that 3-hydroxyhexane-2, 5-dione is further metabolized to non-glycating species in human blood. The discovery represents a new direction within non-enzymatic metabolism and within the use of alkyne-tagging for metabolism studies and it revitalizes acetoacetate as a competent endogenous carbon nucleophile. Graphical Abstract: Highlights: In vivo reaction between MG and AcAcO yields the novel metabolite 3-HHD The rate of reaction matches that of known pharmacological scavengers of MG A metabolite-alkyne-tagging strategy clarifies the reductive metabolism of 3-HHD MG-scavenging expands the known biological functions of ketone bodies Abstract : Salomón et al. adds a new facet to a historical hypothesis by demonstrating non-enzymatic reaction between the glycolytic side product methylglyoxal and the fatty acid metabolite acetoacetate in vivo, leading to the novel metabolite 3-hydroxy-2, 5-hexanedione. A metabolite-alkyne-tagging strategy elucidates its metabolism and protein post-translational modifications.